(untitled) (Prilozi za orijentalnu filologiju, 2017)
Koncem 19. stoljeÄ‡a jedna grupa Muslimana GradaÄca pokrenula je akciju za obnovu dÅ¾amije koja je u doba osmanske vladavine postojala u gradaÄaÄkoj tvrÄ‘avi. Radi se o najstarijoj gradaÄaÄkoj dÅ¾amiji, koja je kao vjerski objekat sluÅ¾ila, uglavnom, za potrebe tvrÄ‘avske posade, ali se njome sluÅ¾io i dio mahala smjeÅ¡tene oko tvrÄ‘ave. VeÄ‡ koncem osmanske vladavine ova je dÅ¾amija bila zapuÅ¡tena i nalazila se u loÅ¡em stanju, da bi 1878. godine, zaposjedanjem tvrÄ‘ave od strane austrougarske vojske, definitivno prestala sluÅ¾iti svojoj svrsi. Drveni dijelovi dÅ¾amije (munara, krov, prozori, vrata) ili su propali zbog kiÅ¡e i vlage, ili su ih austrougarski vojnici izloÅ¾ili, dok su kameni dijelovi djelomiÄno iskoriÅ¡teni za gradnju Nove ili Reuf-begove dÅ¾amije, koja je prije toga postojala kao mesdÅ¾id, a djelomiÄne za neke druge graÄ‘evine u GradaÄcu. Od 1891. traju pokuÅ¡aji da se obnovi tvrÄ‘avska dÅ¾amija, ali je Zemaljska vlada sredinom 1909. odbacila svaku moguÄ‡nost njezine obnove.—————————————————Destiny of the mosque in the GradaÄac fortress and the attempt of its reconstruction 1891-1909Late in the 19lh century, a group of the GradaÄac Muslims launched a campaign to reconstruct , ie mosque, which in the times of the Ottoman rale existed inside the fortress of GradaÄac. It was the oldest GradaÄac mosque, which as a religious structure served, mainly, the needs of the fortress garrison, but it was also used by a part of the adjacent residential quarters. By the end of the Ottoman rule, the mosque was neglected and was in a poor condition, so that in 1878, with the occupation of the fortress by the Austro- Hungarian army, it definitively ceased to serve its purpose. The wooden parts of the mosque (the minaret, roof, windows, door) were either destroyed by rain and dampness, or the Austro-Hungarian soldiers made fire from them, while the stone parts were partly used for the building of the New alias Reuf- begova mosque, which before that had existed as masjid, and partly for the construction of some other buildings at GradaÄac. From 1891 there have been attempts to reconstruct the fortress mosque, but the Land's Government in the midÄ‘le of 1909 refused any possibility of its reconstmction.